Central Office of Press Control/ Main Control Office of Press, Publication and Performances – background, audit scope and staff - Kamińska-Chełminiak, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The aim of the article was to present the circumstances of the establishment and the scope of activities of the Central Office for Control of the Press, which was transformed into Main Office for Control of the Press, Publications, and Public Performances in November 1945. The article is an attempt at answering the following questions: who were the first censors? From what communities/ professional groups did they come? According to what criteria were the censors selected shortly after the founding of the Center? How did the so-called Soviet advisors influence the process of the emergence of institutional censorship in the Polish territory during World War II?